A critical analysis of the review on antimicrobial resistance report and the infectious disease financing facility - Brogan, David M.; Mossialos, Elias (Globalization and health, 2016)
Over the past year, two major policy initiatives have been introduced focusing on stimulating antibiotic development for human consumption. The European Investment Bank has announced the development of the Infectious Disease Financing Facility (IDFF) and the British government commissioned the Review on Antimicrobial Resistance, led by Jim O’Neill. Each constitutes a major effort by the European community to address the evolving crisis of antimicrobial resistance. Though both have similar goals, the approaches are unique and worthy of consideration. This manuscript utilizes a previously published framework for evaluation of antibiotic incentive plans to clearly identify the strengths and weaknesses of each proposal. The merits of each proposal are evaluated in how they satisfy four key objectives: 1) Improve the overall net present value (NPV) for new antibiotic projects; 2) Enable greater participation of Small to Medium Sized Enterprises (SME); 3) Encourage participation by large pharmaceutical companies; 4) Facilitate cooperation and synergy across the antibiotic market. The IDFF seeks to make forgivable loans to corporations with promising compounds, while the O’Neill group proposes a more comprehensive framework of early stage funding, along with the creation of a stable global market. Ultimately, the proposals may prove complementary and if implemented together may form a more comprehensive plan to address an impending global crisis. Substantial progress will only be made on these efforts if action is taken at an international level, therefore we recommend consideration of these efforts at the upcoming G20 summit.